If $a,b,c$ are rational numbers and if $\displaystyle \left(a+b\sqrt[3]{2}+c\sqrt[3]{4}\right)^3$ is also rational then prove that $ab+bc+ca=0$

My attempt
Binomial expansion is not a good idea because there will be $27$ terms so I tried to prove using factorization.
$$\displaystyle \left(a+b\sqrt[3]{2}+c\sqrt[3]{4}\right)^3-\left(c\sqrt[3]{4}\right)^3 \\=\left(a+ b\sqrt[3]{2}\right)\left[\left(a+b\sqrt[3]{2}+c\sqrt[3]{4}\right)^2+\left(a+b\sqrt[3]{2}+c\sqrt[3]{4}\right)\left(c\sqrt[3]{4}\right)+\left(c\sqrt[3]{4}\right)^2\right]$$

This again leads to complicated calculations. Then I tried to equate it to a rational number $r$.

\begin{align*} \displaystyle \left(a+b\sqrt[3]{2}+c\sqrt[3]{4}\right)^3&=r\\ \implies a+b\sqrt[3]{2}+c\sqrt[3]{4}&=r^{1/3}\\ \implies b\sqrt[3]{2}+c\sqrt[3]{4}&=r^{1/3}-a\\ \implies(b\sqrt[3]{2}+c\sqrt[3]{4})^3&=(r^{1/3}-a)^3\\ \implies2b^3+6\sqrt[3]{2}~b^2c+6\sqrt[3]{4}~bc^2+4c^3&=r-3r^{2/3}a+3r^{1/3}a^2-a^3 \end{align*} When I got stuck here I wrote the equation $a+b\sqrt[3]{2}+c\sqrt[3]{4}=r^{1/3}$ in $3$ different ways, each time multiplying with $\sqrt[3]{2}$ \begin{align*} \displaystyle a+b\sqrt[3]{2}+c\sqrt[3]{4}&=r^{1/3}\\ a\sqrt[3]{2}+b\sqrt[3]{4}+2c&=\sqrt[3]{2}r^{1/3}\\ a\sqrt[3]{4}+2b+2\sqrt[3]{2}c&=\sqrt[3]{4}r^{1/3}\end{align*} I tried adding the above three equations but it wasn't helpful.

Can someone help me in solving the question. Thanks in advance.

Is it possible to generalize the question as $\left(a+b\sqrt[3]{n}+c\sqrt[3]{n^2}\right)^3$ where $n$ is a non-square integer?

  • 1
    $\begingroup$ i think it would be tedious, but when you multiply this out, many of the radicals cancel and you can collect like terms fairly nicely $\endgroup$
    – C Squared
    Jul 7, 2021 at 8:25
  • 1
    $\begingroup$ So that the binomial expansion hurts less, I'd call $q = 2^{1/3}$ and simplify any exponent greater than $4$ using that $q^4 = 2q$. You can also ignore all rational terms, so you end up only with an equation with six terms, three with $q$ and three with $q^2$. $\endgroup$
    – AnilCh
    Jul 7, 2021 at 8:34
  • 1
    $\begingroup$ @CSquared I got this question from a book for contest maths, so it's more likely that there will be a solution without expanding the expression. $\endgroup$
    – Asher2211
    Jul 7, 2021 at 8:35
  • $\begingroup$ you could try to look for terms in the expansion which have one factors of $ac$, $bc$, or $ab$ in them and try to deduce something indirectly. $\endgroup$
    – C Squared
    Jul 7, 2021 at 8:40
  • $\begingroup$ Note: In your factorization, the second term should have a minus sign. $\endgroup$
    – Calvin Lin
    Jul 7, 2021 at 15:04

1 Answer 1


By using $$(x+y+z)^3=x^3+y^3+z^3+3xy(x+y)+3xz(x+z)+3yz(y+z)+6xyz$$ we get $a^2b+2b^2c+2ac^2=0$ and $ab^2+a^2c+2bc^2=0$. Now multiply the first equation by $b$ and the second by $a$ and then subtract them. We obtain $c=0$ (and then $a=0$ or $b=0$) or $a=b=0$.

Edit. I forgot to mention that I used the following: if $p+q\sqrt[3]{2}+r\sqrt[3]{4}=0$, with $p,q,r$ rational numbers, then $p=q=r=0$.

The generalization is straightforward.

  • 1
    $\begingroup$ It seems to me that the goal is to prove $ab+bc+ca=0$ without proving that two among $a,b,c$ are zero. $\endgroup$
    – lhf
    Jul 7, 2021 at 16:09
  • 1
    $\begingroup$ @lhf You can give it a try. $\endgroup$
    – user26857
    Jul 7, 2021 at 17:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.